Implementasi Metode Taboo Code Untuk Kompresi File Video - Simanjuntak, Saiful (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Video is a technology for capturing, recording, processing, and rearranging images usually using electronic signals, or digital media. For example, a video file that is large in size causes the sending process to take longer, and uses a large amount of memory space in its storage. Problems that arise due to the large file size include the wasteful storage media used, as well as more time in terms of data exchange, data transfer via the internet is a big problem in Indonesia because download and upload speeds are very low. To overcome this problem, data compression techniques are needed. The concept of compression was born as a real solution to the problem of the amount of space needed to store various digital files, including video files. Compression technique is a technique that compresses files so that their size becomes smaller while maintaining the quality of the representation of the filet.